Study on Carbon Emission and Its Influencing Factors in Island Countryside - LIU Wenxiu; GUO Xu; HUANG Shengmin; ZHAO Jinming; ZHU Mengyu (Haiyang Kaifa yu guanli)
Realizing the goal of “double carbon” and promoting the strategy of rural revitalization is an important theme of Chinese modernization in the new era. At present, the implementation of ecological dual-carbon policy in island fishing villages faces various challenges and opportunities. Zhoushan is based on “island and countryside” to comprehensively explore the sustainable development path of low-carbon agriculture and low-carbon countryside. In this paper, entropy method is used to study the influencing factors of rural carbon emissions on Zhoushan Island. The results show that: in the element layer, manufacturing industry, aquaculture, residential accommodation, livestock and poultry breeding, transportation, other service industries, farming and planting, and domestic electricity consumption are ranked in order. The criterion layer ranks rural industry, agricultural industry, and resident life in order. Therefore, different regional characteristics, as well as changes in rural social and economic development and lifestyle, lead to different carbon emissions. Finally, some strategies are put forward for island villages carbon emissions development.